Molecular investigation of feline herpesvirus 1 (fhv-1) and feline calicivirus in cats with respiratory system problem - Seval Bilge Dağalp; Fırat Doğan; Touraj Aligholipour Farzani; Ali Rıza Babaoğlu; Gülizar Acar Kırmızı; Mehmet Çabalar (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate the presence / prevalence of these infections in FHV (Feline Herpesvirus) and FCV (Feline Calicivirus) suspected samples, to correlate them with reported symptoms and molecular characterization of these viruses. Materials and Methods: For this purpose, a total of 119 specimens were collected from 70 from cats clinically showing respiratory system problem, 31 nasal, 30 conjunctival, 8 oral, 7 orafarengeal and 11 rectal swaps and 32 EDTA blood samples. Viral nucleic acid extraction was performed from the samples and the presence of these infections was investigated by PCR. Samples with positive results were subjected to sequence analysis for molecular characterization. Results: Sampled cats were evaluated as positive for 45.71% (32/70) FHV-1 and 10% (7/70) FCV. 4,29% (3/70) of these cats were positive for both infections. FHV-1 infection was more common in cats with respiratory system findings. While age-conscious cats were observed in all age groups; especially oral and / or orafarengeal swap samples were found to be sensitive samples in the diagnosis of both infections. Conclusion: These infections, as well as being seen in infected cats, can also be detected in healthy-looking animals and it should be noted that this should not be ignored in the transmission of these infections. Therefore, in order to reduce the severity of the clinical symptoms, to minimize the scattering and persistence, it is necessary to focus on the regular vaccination of the cats that live together, especially in the community. In addition, factors other than FHV and FCV (bacteria such as M.felis, C.felis, B.bronchoseptica) can be found in cats with respiratory, eye and oral lesions and these factors should be checked in infected cats.